Using a Blended Learning Approach to Encourage Course Interaction in a First-Year Business Communication Module - Mdletye, Zizipho; Usadolo, Sam Erevbenagie (Research in Social Sciences and Technology- OpenED Network, 2024)
The aim of the study is to examine the effectiveness of blended learning in encouraging course interaction amongst first-year students studying a business communication module. The COVID-19 pandemic resulted in the increased use of blended learning as a teaching approach to encourage learning regardless of the location. Existing research on blended learning suggests its value in promoting increased student engagement, ultimately contributing to positive educational outcomes. Data was collected through a cross-sectional survey whereby a questionnaire was distributed to the respondents using Google Forms. Data was analysed on the same platform. Cross-tabulation was used to understand the relationships between factors in participants’ responses to the questions. Results indicate that blended learning successfully drives course interaction because the combination of class-based and online engagement positively impacts how likely students are to engage in course content. This paper makes a valuable contribution in the form of underscoring a pressing need for research that is aimed at understanding how blended learning shapes the experiences students have with their modules, as well as how these factors may shape current practices in blended learning. Most students indicated that they would recommend blended learning as it increased participation and engagement with their course content.